Detecting lenticulostriate artery lesions in patients with acute ischemic stroke using high-resolution MRA at 7 T. Issue 3 (April 2019) - Miyazawa, Haruna; Natori, Tatsunori; Kameda, Hiroyuki; Sasaki, Makoto; Ohba, Hideki; Narumi, Shinsuke; Ito, Kohei; Sato, Mitsunobu; Suzuki, Takafumi; Tsuda, Keisuke; Yoshioka, Kunihiro; Terayama, Yasuo
Background: Recent advances in high-resolution (HR) magnetic resonance angiography (MRA) using ultrahigh-field systems enable direct visualization of the lenticulostriate arteries (LSAs), which had been hardly achieved by conventional MRA. Hence, by using HR-MRA at 7 T, we attempted to assess occlusive changes in the LSAs in patients with LSA territorial infarcts. Methods: We prospectively examined 34 consecutive patients with acute ischemic stroke in the LSA territory using a 7 T scanner. We measured the lengths of the relevant LSAs on HR-MRA and the diameters/volume of the infarcts and compared these between the patients with/without occlusive changes in the LSAs. Results: On HR-MRA, occlusion of the LSAs was observed in 19 (59%) of 32 patients who were eligible for the analyses. The curved/straight lengths of the LSAs in the patients with LSA occlusion (23.1–31.1/17.8–24.3 mm) were significantly shorter than in those without apparent LSA occlusion (25.8–39.5/24.0–30.4 mm) ( P  = 0.027/0.003). The anteroposterior/superoinferior diameters of the infarcts were significantly larger in the occluded-LSA group (14.5–21.4/14.9–22.2 mm) than in the intact-LSA group (10.9–16.8/10.8–16.2 mm) ( P  = 0.041/0.011). In addition, the curved lengths of the relevant LSAs showed significant correlations with the superoinferior diameters of the infarcts ( r  = 0.38, P  = 0.034). Conclusion: Occlusive changes in the LSAs were frequently found in patients with acute ischemic stroke within the LSA territory when using HR-MRA at 7 T and were substantially related to superoinferior extension of the infarcts.